2020
DOI: 10.48084/etasr.3246
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Electric and Dielectric Behavior of PVC Composites

Abstract: Polyvinyl chloride (PVC) is usually used as insulation in electrical engineering, mainly as cable insulation sheaths. A method for improving PVC’s dielectric properties, reducing the effects of UV aging, is the use of PVC films doped in alumina and titanium dioxide. This research investigated the influence of alumina and titanium dioxide (Al2O3/TiO2) on the dielectric properties of PVC. Four PVC samples were examined using an RLC impedance analyzer. Fourier Transform Infrared (FTIR) spectroscopy was utilized o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…As demonstrated in Figure 4, for a frequency of 100Hz, the values of Ɛ r for BaTiO 3 , TiO 2 , CaCO 3 , and Al 2 O 3 decrease by approximately 57%, 50%, 35%, and 37%, respectively, compared to the value of Ɛ r for pure PVC prior to aging. These findings are in agreement with the findings of [13,25,33], and can be validated through (1) [1]:…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…As demonstrated in Figure 4, for a frequency of 100Hz, the values of Ɛ r for BaTiO 3 , TiO 2 , CaCO 3 , and Al 2 O 3 decrease by approximately 57%, 50%, 35%, and 37%, respectively, compared to the value of Ɛ r for pure PVC prior to aging. These findings are in agreement with the findings of [13,25,33], and can be validated through (1) [1]:…”
Section: Discussionsupporting
confidence: 89%
“…Metal oxide nanoparticles in polymers have been studied as alternative materials for electrical applications [8][9][10][11]. Studies have demonstrated that the incorporation of nanoparticles in similar systems can have both positive and negative effects on breakdown strength [12][13][14]. Furthermore, it has been established that the production of artificial reinforcement fillers can lead to either an increase or decrease in the dielectric strength of polymeric composite insulation, which is utilized in high voltage outdoor applications [15].…”
Section: Introductionmentioning
confidence: 99%
“…The same disparity was found in [31][32][33]. Sr 0.55 Na 0.45 SiO 3 has an activation energy of www.etasr.com Najim: Synthesis and Electrical Behavior of Sodium Doped Monoclinic SrSiO 3 0.39 eV and its conductivity at 700C is higher (1.73×10 -2 Scm -1 ) than that of other solid electrolytes such as La 0.9 Sr 0.1 In 0.8 Mg 0.2 O 3 (10 -3 Scm -1 ), La 0.9 K 0.1 Ga 0.9 Mg 0.1 O 3 (7.65×10 -3 Scm -1 ), and La 0.9 Ca 0.1 InO 3 (1.6×10 -3 Scm -1 ) [34][35][36][37][38].…”
Section: Resultsmentioning
confidence: 94%